Image_2.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The Versova-Madh ferry service is used by a wide range of commuters, some even plying two-wheelers stacked on the flat decks. Daily commuters include students going to school, daily wage labourers, working professionals, and fisherwomen with their daily catch headed for the markets.